2012
DOI: 10.1111/j.1365-2745.2012.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination mode predicts phenological response to climate change in terrestrial orchids: a case study from central Europe

Abstract: Summary1. Herbarium collections contain long-term data for a wide range of taxa and provide unique opportunities to evaluate the importance of life-history components in driving species-specific responses to climate change. In this paper, we analyse the relationships between change in flowering dates and life-history traits within a phylogenetic framework. The study is based on an extensive data set of herbarium specimens of orchids collected in Hungary between 1837 and 2009, supplemented by recent field obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 72 publications
1
74
0
7
Order By: Relevance
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
mentioning
confidence: 99%
“…Although phenological analyses of herbarium data offer unique insights into past responses, they model past responses only, and long-term phenological observation is necessary to fully understand present responses and model those in the future. To complement the herbarium data and test our models, we are directly monitoring Rhododendron phenology on Yulong Mountain, conducting artificial warming experiments, and documenting indigenous peoples' observations of change.This study joins other work from the past decade showing the value of herbarium collections to infer long-term phenology (10,11,43,48,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These have increasingly shown that not only can the "messy" data from herbarium collections be used to infer phenology, but that these data can reveal the complex effects on phenology of geography (43), pollination (62), morphological traits (48, 52), and, in this study, the contrasting response of warming across different seasons.…”
mentioning
confidence: 99%
“…Ez az oka, hogy az 1990-es évek közepéig Magyarországon az egyetlen publikált H. adriaticum lelőhely a Szabó István által 1974-ben megtalált és H. hircinum néven közölt (SZABÓ 1987) Pilikán-Szoroshadi állomány volt (MOLNÁR V. et al 1995). Szisztematikus munkával, az irodalmi és herbáriumi adatok feldolgozásával és a lelőhelyek felkeresésével újabb állományok kerültek elő, melyekről átfogó képet nyújtott SULYOK et al (1998).…”
Section: Bevezetésunclassified
“…A faj herbáriumi adatai a Magyarországi Orchideák Herbáriumi Adatbázisából (MOLNÁR V. et al 2012) származnak. A fajjal kapcsolatos terepi vizsgálatokat 1992-ben kezdtem a keszthelyi állományban, a többi hazai termőhelyre kiterjedő adatgyűjtések -már segítőkkel -2010-től folynak.…”
Section: Anyag éS Módszerunclassified
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Even if the distribution of H. hircinum and its relatives is indeed particularly responsive to climate change, their phenology appears to us to be more robust. In Hungary at least, H. adriaticum -the sister species of H. hircinum -has proven to be less susceptible than most species of Orchidinae to phenological shifts in presumed responses to climate change (Molnár et al, 2012b). In this context, it is interesting to note that the typical altitude of H. hircinum populations appears to increase with decreasing latitude.…”
Section: Evidence For Climatic Drivers Of Northward Migrationmentioning
confidence: 99%